Two-dimensional simulation of microsecond-timescale underwater electrical explosion of a copper wire. (6th October 2022) - Shi, Huantong; Li, Tuan; Hu, Yujia; Li, Xingwen; Wu, Jian; Chen, Li; Qiu, Aici
Abstract: Underwater electrical wire explosion (UEWE) is an efficient source of underwater shock waves (SWs). In order to efficiently simulate the interaction between the UEWE SW and structures, a coupled model that includes the electric circuit, the exploding wire and the surrounding water is established based on user-subroutines provided by the commercial explicit dynamics software ANSYS AUTODYN. The modeling starts from room temperature by using the tabular wide-range metal equation of state (EOS) and conductivity data. Experimental validation is performed with copper wires exploded by a μ s-timescale pulsed discharge. The numerical results show satisfactory consistency with experiments in terms of the current and voltage waveforms, the wire expansion trajectory, the evolution of SW front, the interaction between SW and electrodes and the SW pressure profiles. The main discrepancy lies in the SW amplitude that is ∼20% higher in the calculation and the possible reasons are discussed in detail. Based on this approach and with proper modifications to the metal EOS and conductivity data, the interaction between UEWE SWs and structures can be efficiently modeled in 2D and 3D for practical applications.